Reduction of Sidelobes by Nonuniform Elements Spacing of a Spherical Antenna Array - S. Rupcic; V. Mandric; D. Zagar (Radioengineering, 2011)
This paper presents a significant sidelobe reduction if nonuniform elevational spacing of antenna elements on the sphere is used. Antenna elements are progressively phased with a uniform amplitude excitation. The calculation of the required element position is presented. The achieved sidelobe level reduction with unequally spaced arrays could reach even more than 20dB difference with regard to the first significant sidelobe level of equally spaced arrays. By this method, arrays have the ability to produce the desired radiation pattern and could satisfy requirements for many applications.